Effectiveness of UEFA's regulation for European football financial management: A comprehensive systematic review and meta-analysis - Jorge Martín-Magdalena; Susana De los Ríos-Sastre; Raquel Redondo; David Alaminos (Heliyon)
Background: The Union of European Football Association's (UEFA) Financial Fair Play (FFP) regulations are a topic of ongoing debate. This study aims to evaluate and quantify the FFP's effect on clubs' financial performance and critically review the regulatory changes introduced by the UEFA in 2022 through the new Financial Sustainability Regulations (FSR). Methods: A systematic review and meta-analysis were conducted using the Web of Science and Scopus databases up to December 31, 2023, following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement. Results: This systematic review included 22 articles; a meta-analysis was conducted on 52 financial measures derived from 20 studies of 11 articles. The meta-analysis’ main result—obtained by comparing two different financial measures (profitability versus solvency)—revealed that FFP's effect on profitability measures was significant, with a value of 0.151 (p = 0.050); however, the effect size for solvency measures was not significant, with a value of 0.049 (p = 0.639). Contributions: This systematic review revealed variability in the results of the studies analysed, reflecting contextual factors' influence, which underlines the need for a more adaptive and specific approach to clubs’ financial control policies. The meta-analysis found that the type of financial measure employed (profitability versus solvency) was a notable source of variability among the studies, as its moderating effect was significant. Consequently, the FFP exerted contrasting effects on profitability and solvency. Limitations: A significant level of heterogeneity was observed in the financial measures analysed, predominantly because of the different samples and periods across the included studies. Conclusions: This study corroborates FFP's mixed and limited impact on financial performance, highlighting the need for stricter control in European football, which aligns with the new FSR. Our study underscores aspects that future research should address to deepen knowledge of UEFA regulations' efficiency in enhancing football's financial sustainability.